Phase 3 clinical trial investigating the effect of selenium supplementation in men at high‐risk for prostate cancer. Issue 3 (10th August 2012) - Algotar, Amit M.; Stratton, M. Suzanne; Ahmann, Frederick. R.; Ranger‐Moore, James; Nagle, Raymond B.; Thompson, Patricia A.; Slate, Elizabeth; Hsu, Chiu H.; Dalkin, Bruce L.; Sindhwani, Puneet; Holmes, Michael A.; Tuckey, John A.; et al.
Abstract PURPOSE This study was conducted to investigate the effect of Se supplementation on prostate cancer incidence in men at high risk for prostate cancer. METHODS A Phase 3 randomized, double‐blind, placebo‐controlled clinical trial was conducted in 699 men at high risk for prostate cancer (prostate specific antigen (PSA) >4 ng/ml and/or suspicious digital rectal examination and/or PSA velocity >0.75 ng/ml/year), but with a negative prostate biopsy. Participants were randomized to receive daily oral placebo (N = 232), 200 µg selenium (N = 234), or 400 µg selenium (N = 233) as selenized yeast. They were followed every 6 months for up to 5 years. The time to diagnosis of prostate cancer was compared between treatment groups using the Cox proportional hazards model. RESULT Compared to placebo, the hazard ratios [95% confidence intervals] for risk of developing prostate cancer in the selenium 200 µg/day or the selenium 400 µg/day group were 0.94 [0.52, 1.7] and 0.90 [0.48, 1.7], respectively. PSA velocity in the selenium arms was not significantly different from that observed in the placebo group (P = 0.18 and P = 0.17, respectively). CONCLUSION Selenium supplementation appeared to have no effect on the incidence of prostate cancer in men at high risk. In conjunction with results of other studies, these data indicate that selenium supplementation may not have a role in prostate cancer chemoprevention. Prostate 73: 328–335, 2013. © 2012 Wiley Periodicals, Inc.